Penipuan Berkedok Investasi Jenis Binary Option - Muhammad Ajirifano Sahubawa; Deassy Jacomina Anthoneta Hehanussa; Jacob Hattu (PATTIMURA Law Study Review, 2023)
ABSTRACT: Fraud under the guise of Binary Option type Investment is one of the many scams under the guise of investment. To find out the modus operandi of fraud under the guise of investment, especially the type of Binary Option as well as legal remedies and legal protection from victims of fraud under the guise of investment of the Binary Option type, this research was made as an effort to prevent the public from financial losses due to fraud under the guise of investment. The research method used in this study is normative juridical with statutory, conceptual and case approaches. The legal materials used are primary, secondary and tertiary legal materials which are analyzed qualitatively. The results of the study show that Binary Option investment is a form of online gambling disguised as an investment. Therefore, everyone who introduces and promotes Binary Options trading and similar things as an investment is clearly a fraud who wants to seek personal gain. Therefore, this research is needed to increase public literacy regarding investment as an effort to eradicate fraud under the guise of investment. Various modus operandi carried out by the perpetrator in an effort to smooth out the action, namely; creating and distributing social media content containing misleading information regarding the Binomo platform, creating fictitious trading courses, and trading fictitious trading robots. In addition, related legal remedies that can be taken to avoid Binary Option investment fraud are preventive legal remedies, which are carried out by reporting and categorizing all forms of investment offers that have a mechanism and system similar to Binary Options as a form of online gambling that violates statutory provisions.